2021
DOI: 10.1093/ageing/afab018
|View full text |Cite
|
Sign up to set email alerts
|

Frailty is associated with in-hospital mortality in older hospitalised COVID-19 patients in the Netherlands: the COVID-OLD study

Abstract: Background During the first wave of the COVID-19 pandemic older patients had an increased risk of hospitalisation and death. Reports on the association of frailty with poor outcome have been conflicting. Objective The aim of the present study was to investigate the independent association between frailty and in-hospital mortality in older hospitalised COVID-19 patients in the Netherlands. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 20 publications
(20 reference statements)
2
79
1
Order By: Relevance
“…Finally, 22 sources were included in our final analysis 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 . The process used to select study sources is presented in Figure 1 through a PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 22 sources were included in our final analysis 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 . The process used to select study sources is presented in Figure 1 through a PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that CFS, but not age, remained independently associated with mortality [23]. Three other studies demonstrated higher in-patient mortality in older and frail patients [12,24,25]. Furthermore, a recent meta-analysis showed that each 1-point increase in CFS was associated with 12% increase in mortality in a linear fashion [26].…”
Section: Discussionmentioning
confidence: 99%
“…Six (11.5%) studies reported unadjusted associations between frailty based on the CFS and receipt of mechanical ventilation (OR 0.32, 95% CI 0.08-1.30; I 2 = 89%; Figure S9). 37,40,43,48,60,64 No studies reported data related to functional outcomes, disability, or quality of life.…”
Section: Health Outcomesmentioning
confidence: 99%